Development of a Hetero‐Bimetallic Phillips‐Type Catalyst for Ethylene Polymerization. Issue 12 (16th July 2013) - Zeng, Yanning; Matta, Akanksha; Dwivedi, Sumant; Taniike, Toshiaki; Terano, Minoru
<x xml:space="preserve">Abstract</x> In order to improve the ethylene polymerization activity and branching ability of Phillips catalysts, various bimetallic catalysts were synthesized on the basis of co‐impregnation of chromium and second metal salts. The activity and branching ability of the catalysts were enhanced by the introduction of zirconium, zinc, and vanadium, while deteriorated by the introduction of molybdenum and tungsten. On the other hand, the structure of metal salt precursors did not greatly affect the catalytic performances. X‐ray photoelectron spectroscopy (XPS) clarified a tendency that second metal with lower electronegativity decreased the electron density on chromium species, resulting in higher polymerization activity of the bimetallic catalysts plausibly due to enhanced ethylene activation. On the other hand, the branching ability of the catalyst improved as the catalyst activity increased due to more facile formation of α‐olefin co‐monomer.<inline-graphic xlink:href="ark:/27927/pgg3zr5bcb1" content-type="mren201300119-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />